EVALUATION OF THE LENGTH OF THE VEGETATION PERIOD OF THE POTATO - Plich, Jarosław (Plant Breeding and Seed Science, 2017)
Potato cultivars are classified into maturity groups according to the length of the vegetation period re-quired to produce a harvestable product. Although accurate classification of potato cultivars to a specific maturity group is of great practical importance, there is no standard method to characterize the maturity type of potato cultivars. In this work, the method of evaluation of vegetation period routinely used at IHAR-PIB, Młochów Research Center is described.